Orthopedic trauma call for the attending surgeon - Hak, David J.; Ipaktchi, Kyros R.; Morgan, Steven J. (Slack Incorporated, 2013)
Drs. David J. Hak, Kyros R. Ipaktchi and Steven Morgan are joined by over 50 leading experts to provide a succinct and quick review of the key points that will allow you to provide patients with expert and immediate care. Inside this book each chapter is written in an easy to read bulleted format that will allow for a quick review of the key facts you need to know while taking call. Chapters also cover emergent and definitive management and provide guidelines for when to consider referral to a higher level of care. The authors also share their tips and tricks for successful outcomes, while highlighting potential pitfalls and how to avoid them. Since it can be difficult to find time to read a traditional textbook or review article.